2019
DOI: 10.1002/bin.1657
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of treatments for vocal stereotypy: Response interruption and redirection and response cost

Abstract: The purpose of this study was to expand on research on treatments for stereotypy by evaluating the effects of response interruption and redirection (RIRD) and response cost (RC) alone and as a treatment package on vocal stereotypy. Treatment phases included RIRD, RC, and response interruption and redirection plus response cost (RIRD + RC).The efficacy of these treatments was determined by measuring duration of stereotypy in session and during treatment intervals. Vocal stereotypy decreased in all three treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This pairing, or conditioning, of the neutral stimulus inevitably became a signal to the participant for the cessation of VS during the presentation of the signal stimulus, while simultaneously decreasing the necessity of the procedures in future presentations (Haley et al., 2010). Neutral stimuli often included a colored item such as a wristband (e.g., McNamara & Cividini‐Motta, 2019), shirts and curtains (e.g., Saini et al., 2015), construction paper (e.g., Schumacher & Rapp, 2011) or non‐color related items such as a sports watch (e.g., Healy et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pairing, or conditioning, of the neutral stimulus inevitably became a signal to the participant for the cessation of VS during the presentation of the signal stimulus, while simultaneously decreasing the necessity of the procedures in future presentations (Haley et al., 2010). Neutral stimuli often included a colored item such as a wristband (e.g., McNamara & Cividini‐Motta, 2019), shirts and curtains (e.g., Saini et al., 2015), construction paper (e.g., Schumacher & Rapp, 2011) or non‐color related items such as a sports watch (e.g., Healy et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Further assessment is required to determine how best to categorize this intervention. It should also be noted that two additional studies compared the measurement methods (i.e., interrupted, whole session ) used in RIRD studies (McNamara & Cividini‐Motta, 2019; Toper‐Korkmaz et al., 2018) and did not find differences between the two measurement types. However, as these interventions included additional elements (i.e., stimulus control and/or response cost), the analysis is not directly comparable to the original intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, we did not collect data on either treatment fidelity of RIRD implementation or social validity of the outcomes. Prior studies have socially validated the immediate decreases in VS produced with RIRD (Cassella et al, 2011; Gibbs et al, 2018; McNamara & Cividini-Motta, 2019), whereas the purpose of the present study was to determine if subsequent changes were detectable. To that end, a logical next step would be to determine whether subsequent changes are socially significant (i.e., detectable to stakeholders).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, with regard to procedural variations and future considerations, the current study did not include toy removal contingent on vocal stereotypy as a component of RIRD, nor did it include programming for appropriate vocalizations. Being that McNamara and Cividini‐Motta (2018) indicated the benefit of toy removal contingent on vocal stereotypy, and Colón et al (2012), indicated that training for appropriate vocalizations can enhance RIRD treatment outcome, it would be beneficial to determine how treatment consistency errors may affect other procedural variations and dependent variables. One further limitation is that although contingent toy removal was not included in the current procedures, implementation of motor redirection may have resulted in less opportunities to manipulate the leisure item.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that appropriate vocalizations increased for three of the four participants. Since then, several studies have further examined the effects of RIRD inclusive of some procedural variations (e.g., Ahrens, Lerman, Kodak, Worsdell, & Keegan, 2011;Athens, Vollmer, Sloman, & Pipkin, 2008;Colón & Ahearn, 2019;Colón, Ahearn, Clark, & Masalsky, 2012;Dickman, Bright, Montgomery, & Miguel, 2012;Duffy-Cassella, Sidener, Sidener, & Progar, 2011;Love, Miguel, Fernand, & LaBrie, 2012;McNamara & Cividini-Motta, 2018;Miguel, Clark, Tereshko, & Ahearn, 2009;Schumacher & Rapp, 2011;Shawler & Miguel, 2015). For instance, Ahrens et al extended the findings of Ahearn et al by evaluating redirection using both vocal (matched) and motor (unmatched) instructions to treat vocal stereotypy.…”
mentioning
confidence: 99%